Utilization of wood biomass residues from fruit tree branches, evergreen hardwood shrubs, and Greek fir wood as raw materials for particleboard production. Part B. Hygroscopic properties and formaldehyde content. Issue 5 (19th October 2016) - Lykidis, Charalampos; Barboutis, Ioannis; Grigoriou, Athanasios
Abstract: This paper investigates the basic hygroscopic properties and formaldehyde content (FC) of particleboards produced with wood biomass from fruit tree branches and evergreen hardwood shrubs as substitute raw materials for fir particles. One-layer laboratory particleboards with two distinct target densities (0.63 g/cm 3 and 0.69 g/cm 3 ) were produced using various mixtures of the above materials. Industrially produced wood particles were also used for comparison purposes. The results showed that the replacement of fir wood (FW) by evergreen hardwood material significantly upgraded board's quality in terms of thickness swelling (TS) and water absorption (WA) (except boards with density of 0.63 g/cm 3 ) after immersion in water for 24 h and residual swelling (RS) after reconditioning. The contribution of branch-wood (BW) particles in the production of FW boards with density of 0.63 g/cm 3 induced increase of TS, WA, and RS while for boards with density of 0.69 g/cm 3 did not result to significant changes except for RS. In terms of FC, boards made of BW and evergreen hardwood showed significantly lower FC compared to those produced by FW and industrial particles.